Пространства Марины Цветаевой - Voitekhovich, Roman (Studia Rossica Posnaniensia, 2021)
The hallmarks of space in Tsvetaeva’s poetic world are vertical orientation, two-worldness (many-worldness), measurability, and “immensity”, often expressed by asymmetry. Tsvetaeva’s model of the double world is presented both in its pure form and in a multilayer one (the model of “matryoshka” according to Lotman) with a hierarchical vertical correlation of spaces. The vertical sets the plots, stylistics, system of characters, system of time and expectations of the reader. Tsvetaeva is a bright representative of irrational tendencies in art, which manifest themselves against the background of rational ones, through their violation. Thus, The Attempt of a Room (1926) builds on an imaginary effort to present a hexagonal box of a rendezvous, but fails. The last poem I Keep Repeating the First Verse… (1940) is a poetic reaction to the “mistake in counting”: there should be not six but seven souls at the table. In one of her poems, Tsvetaeva calls herself “one who has edited the miracle with numbers”. This formula aphoristically expresses the nature of creativity as first intuitive search, and then rational design. The mathematical calculation of the composition of her books is an analogue of the metric-stanzaic “frame” of her lyrics. In the given proportions she often uses a deliberate failure by one unit (for example, in the collection From Two Books she adds one extra poem, which was originally missing in these two books).